Good soldiers and good actors: the influence of motivation and culture on the outcomes of organisational citizenship behaviours - Watters, Aurora (2012)
Past research on organisational citizenship behaviours (OCBs) has often prescribed to a number of preconceived assumptions predominately focused on the positive aspects of OCB performance. Using a sequential mixed-method approach, this thesis tests some of these assumptions considering whether researchers, organisations and other stakeholder should subscribe to the notion that OCBs are always positive. Specifically the thesis examines how OCBs are conceptualised by the employees who experience them in their organisational lives and the extent that culture plays in performance and outcomes of OCB. Study one interviewed five British and five Asian participants on their experiences and conceptualisation of OCBs. The interviews were analysed using the Grounded Theory approach which allowed two main theories to emerge from the data. Firstly, congruence or incongruence of employee and supervisor perceptions of OCB as in or extra role effects the motivation, performance and outcomes. Secondly, employees perform impression management motivated OCBs to facilitate the obtainment of their goals. In addition, cultural differences between the responses of the British and Asian participants were found, suggesting a more complex cultural relationship. Based on these findings, the second study presented OCB and impression management scenarios to 64 British participants and 70 Indonesian participants. The results of this study found that participants were able to distinguish between OCB and impression management behaviours. In addition, the perception of these behaviours as OCB or impression management affected the outcome of the behaviours. British participants' ratings of the effect of OCB and impression management behaviours were found to be more distinct than their Indonesian counterparts, suggesting that Indonesian employees may be more accepting of their co-workers performance of impression management behaviours. The final study examined the relationship between OCB motives, performance and outcomes of OCB performance by 141 Indonesian employees. Results showed that prosocial motives predicted the performance of affiliative and challenging behaviours; however other OCB motives did not predict OCB performance. In addition, affiliative and challenging behaviours predicted positive outcomes for employees, while compulsory citizenship behaviours were associated with negative outcomes. Collectivists and individualists were found to react in converse manners to the performance of affiliative and challenging behaviours. The findings of this thesis found some support for the basic assumptions of OCBs; however, the findings also found contradictions to the assumptions, as well as identifying cultural differences in the conceptualisation, performance and outcomes to OCB performance.